CHRDL1 regulates stemness in glioma stem-like cells - Berglar, Inka; Hehlgans, Stephanie; Wehle, Andrej; Roth, Caterina; Herold-Mende, Christel; Rödel, Franz; Kögel, Donat; Linder, Benedikt (Cells, 2022)
Glioblastoma (GBM) still presents as one of the most aggressive tumours in the brain, which despite enormous research efforts, remains incurable today. As many theories evolve around the persistent recurrence of this malignancy, the assumption of a small population of cells with a stem-like phenotype remains a key driver of its infiltrative nature. In this article, we research Chordin-like 1 (CHRDL1), a secreted protein, as a potential key regulator of the glioma stem-like cell (GSC) phenotype. It has been shown that CHRDL1 antagonizes the function of bone morphogenic protein 4 (BMP4), which induces GSC differentiation and, hence, reduces tumorigenicity. We, therefore, employed two previously described GSCs spheroid cultures and depleted them of CHRDL1 using the stable transduction of a CHRDL1-targeting shRNA. We show with in vitro cell-based assays (MTT, limiting dilution, and sphere formation assays), Western blots, irradiation procedures, and quantitative real-time PCR that the depletion of the secreted BMP4 antagonist CHRDL1 prominently decreases functional and molecular stemness traits resulting in enhanced radiation sensitivity. As a result, we postulate CHRDL1 as an enforcer of stemness in GSCs and find additional evidence that high CHRDL1 expression might also serve as a marker protein to determine BMP4 susceptibility.